ADMINISTRATION OF RED ROSELLAâS PETALS EXTRACT (Hibiscus sabdariffa) INCREASE LEVEL OF SUPEROXIDE DISMUTASE (SOD) WISTAR RATS WHICH INDUCED BY REPETEADLY HEATED COOKING OIL - Herdiani, Novera; Wirjatmadi, Bambang; Adriani, Merryana (Universitas Wijaya Kusuma Surabaya, 2015)
Background: Â repeatedly heated cooking oil is cooking oil that is used many times, had saturated fatty acids containing free radicals. Red rosella petals extract contains antioxidants to minimize the effects of repeatedly heated cooking oil that can raise the levels of SOD. The aim of this study was to analyzed the effect of red rosellaâsÂ petals extract againstÂ oxidative stress of WistarÂ ratsÂ wereÂ induced by repeatedly heated cooking oil with examine levels of Â serumÂ SOD.This research was conducted True Experimental Laboratory with a completely randomized design (CRD) and use the post test. The sample consisted of 24 male rats were divided 4 groups: negative control (fed with standard diet); positive control (fed with standard diet + administered by repeatedly heated cooking oil as much as 2.1 ml / kg bw); treatment group dose I (fed with standard diet + administered by red rosella extract dose 540 mg / kg bw + repeatedly heated cooking oil as much as 2.1 ml / kg bw), and treatment group dose II (fed with standard diet + administered by red rosella extract dose 810 mg / kg bw + repeatedly heated cooking oil as much as 2.1 ml / kg bw). Analysis of data using statistical test One Way ANOVA and Tukey HSD (Î± = 0.05).Results: There were significant differences (p = 0.000) between groups. Red rosella extract treatment group dose 810 mg / kg bw and 540 mg / kg bw were significantly different from the positive control (p = 0.000). Red rosella extract group dose 540 mg / kg bw was significantly different from the negative control (p = 0.000). Red rosella extract group dosage of 810 mg / kg bw was not differ significantly from the control group (p = 0.171).Conclusion: The red rosellaâs petals extract dose of 810 mg / kg bw and dose of 540 mg / kg bw were able to prevent oxidative stress. Optimal deose of red rosella petals extract dose of 810 mg / kg bw was the most effective, because the higher antioxidant activity (67.33%) at dose 810 mg / kg bw dose than 540 mg / kg bw.